Marcus C. Levitt and Tatyana Novikov, eds. Times of Trouble: Violence in Russian Literature and Culture - Walter F. Kolonosky (Studies in 20th & 21st Century Literature, 2010)
While violence is a given in Russian literature and culture, its presence does not suggest that Russian civilization is characterized by a bloody monochromatic hue…
Keywords: violence; Russia; Russian literature; Russian culture